Synthesis, Biological Activity, and Molecular Modelling Studies of Naphthoquinone Derivatives as Promising Anticancer Candidates Targeting COX-2 - Povilas Kavaliauskas; Felipe Stambuk Opazo; Waldo Acevedo; Ruta Petraitiene; Birutė Grybaitė; Kazimieras Anusevičius; Vytautas Mickevičius; Sergey Belyakov; Vidmantas Petraitis (MDPI AG, 2022)
Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-associated mortalities worldwide. Therefore, it is crucial to develop a novel therapeutic option targeting localized and metastatic NSCLC. In this paper, we describe the synthesis and biological activity characterization of naphthoquinone derivatives bearing selective anticancer activity to NSCLC via a COX-2 mediated pathway. The biological evaluation of compounds 9-16 showed promising structure-dependent anticancer activity on A549 cells in 2D and 3D models. Compounds were able to significantly (p < 0.05) reduce the A549 viability after 24 h of treatment in comparison to treated control. Compounds 9 and 16 bearing phenylamino and 4-hydroxyphenylamino substituents demonstrated the most promising anticancer activity and were able to induce mitochondrial damage and ROS formation. Furthermore, most promising compounds showed significantly lower cytotoxicity to non-cancerous Vero cells. The in silico ADMET properties revealed promising drug-like properties of compounds 9 and 16. Both compounds demonstrated favorable predicted GI absorption values, while only 16 was predicted to be permeable through the blood-brain barrier. Molecular modeling studies identified that compound 16 is able to interact with COX-2 in arachidonic acid site. Further studies are needed to better understand the safety and in vivo efficacy of compounds 9 and 16.